Characteristics of regolith developed on basalt in Pahang, Malaysia - Hamdan, J.; Ruhana, B.; McRae, S.G. (Marcel Dekker Inc., 2000)
The characteristics and degree of weathering in a deep regolith developed on basalt were investigated. A representative 15 m deep regolith of soil-saprolite-rock sequence, located in Pahang state, Malaysia, was selected. The intensity of weathering in this deep regolith was assessed by various weathering indices as well as changes in the physicochemical properties and clay mineralogy of the regolith. The values of all weathering indices and other assessments gave strong evidences of intense weathering during saprolite formation. The low CEC and base cation values even in the saprolite layers were accounted by the extreme depletion of major elements such as potassium (K), sodium (Na), calcium (Ca), and magnesium (Mg), and significant enrichment of aluminum (Al), iron (Fe), titanium (Ti), copper (Cu), and niobium (Nb) occurred during saprolitization. The extreme weathering pattern of basalt differed from those described in granite and metamorphic rocks found in Peninsular Malaysia.